PERTUMBUHAN KOTA JEMBER DAN MUNCULNYA BUDAYA PANDHALUNGAN - Edy Burhan Arifin (Faculty of Humanities, Jember University, 2012)
The development of the private plantations during the mid19th in the regency of Jember led to socioeconomic changes among the population. From that moment the indigenous population got the opportunities to make money provided by the large employment the plantation had generated. The development of plantation attracted migrants to come from Madura and other parts of Java and shifted the region’s demographic features from unpopulated to more densely populated. There emerged Madurese culture in North Jember and Javanese culture in the south. In central Jember where the Madurese and Javanese population groups were more or less equal in number, a cultural mix created a hybrid culture called as pandhalungan. Keywords: Jember, urban growth, pandhalungan.